A hierarchical approach for balancing service provision by microgrids aggregators. Issue 2 (2020) - Bella, Alessio La; Bonassi, Fabio; Sandroni, Carlo; Fagiano, Lorenzo; Scattolini, Riccardo
Abstract: Volatile renewable energy resources are gaining more and more diffusion throughout the power system, and their intermittent production calls for enhanced balancing efforts. With a recent regulation, the European Union endorsed the participation of aggregated microgrids to the balancing of power system. The resulting assets optimization problem, however, features privacy constraints that prevent a full exchange of information, making fully centralized approaches not suitable. To this purpose, this work proposes a hierarchical approach allowing microgrids' aggregators to provide balancing services in an efficient and privacy-friendly fashion. This approach is based on a novel method to describe the power exibility that each microgrid can provide, allowing to significantly decrease the computational effort